Exploring gamification as a tool to enhance financial literacy and improve financial behavior - Mohd Hasimi Yaacob,; Nik Aminatun Farhana Zainuddin,; Nurul Hidayah Rohani, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The education sector is changing towards digitalization, notably through the integration of gamification learning techniques in classrooms. This approach has been proven effective in increasing student motivation and engagement. However, the complexity of financial concepts, especially in investment education, can indeed present challenges for students. This study was therefore conducted to assess the effectiveness of gamification in teaching investment subjects. A quantitative survey was conducted using questionnaires distributed to 98 students who participated in the gamified intervention. Data were collected twice, at week 1 and week 10 of the intervention, to compare outcomes and evaluate the impact of gamification. Analysis was conducted using descriptive and inferential statistics, namely paired sample t-test and repeated measures ANOVA. The findings reveal a significant difference between the pre-test and post-test results for all independent variables, indicating the effectiveness of gamification in stock market education. This study highlights that implementing gamification in education has the potential to enhance student motivation, engagement and positive learning experiences, foster goal achievement, improve problem-solving skills, and facilitate the transfer of knowledge and skills.